Moderating Role Leader-Member Exchange Between Emotional Labor and Burnout among Intensive Care Unit Nurses - Andini, Aulia; Trinanda, Okki (Human Resource Management Studies, 2025)
This study aims to analyze the effect of Emotional Labor on Burnout, with Leader-Member Exchange as a moderating variable, among nurses in the Intensive Care Unit (ICU) at RSUP Dr. M. Djamil Kota Padang (Dr. M. Djamil General Hospital, Padang). The research employed a total sampling technique, involving 70 ICU nurses as respondents. Data were collected through a questionnaire using a Likert scale. The data analysis technique utilized was Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software. The findings indicate that: (1) The Surface Acting dimension of Emotional Labor has a significant positive effect on Burnout; (2) The Deep Acting dimension of Emotional Labor has a significant negative effect on Burnout; (3) Leader-Member Exchange has a significant negative effect on Burnout; (4) Leader-Member Exchange significantly and negatively moderates the relationship between Surface Acting and Burnout (5) Leader-Member Exchange significantly and positively moderates the relationship between Deep Acting and Burnout.